Finland : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Financial Policy Transparency, Banking Supervision, Insurance Supervision, Securities Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2001)
Finland has a very sound financial system. Finland is at the forefront of electronic banking and financial sector consolidation. Arrangements for crisis prevention and management need to balance the conflicting goals of minimizing moral hazard and providing adequate safety nets in the financial system. There are some deficiencies as regards compliance with certain of the banking supervision and securities standards. In view of the advanced stage of development of Finland's financial system, supervisory arrangements will need to meet and even exceed international standards.